Existence and Uniqueness Results for Fuzzy Fractional Differential Equation Upon Chinchole-Bhadane Intervals Fractional Calculus Method (Journal of Informatics and Mathematical Sciences, 2023)
In this study, we derive certain features of a novel fractional derivative of two variables presented lately by Chinchole and Bhadane using a Mittag-Leffler kernel. Initially, it is given how to compute the fuzzy set value function’s fractional derivative of the SABC. Hence, it is utilized to show that a solution to a fuzzy fractional differential equation involving the SABC fractional derivative exists and is unique. An example is presented and solved for further illustration.